Docking of 3,5-diphenyl- pyrazoline with monoamine oxidase A receptor and In-Silico structural property calculation - Pratyush, Kumar; Asnani, Alpana (Journal of Drug Delivery and Therapeutics, 2019)
Depression is one of the widely spread disorder in current population and is increasing exponentially. Now age group is not a mandatory clause for depression as children today are also affected. Inhibition of monoamine oxidase A (MAO A) isoform was reported for treating depression by elevating mood. Hydrazines have been also reported for their antidepressant action by inhibiting the monoamine oxidase. In this current study we have chosen 3,5-diphenyl-pyrazoline as ligand molecule which actually mimics the structure of cyclic hydarazine and was supposed to bind with MAO A receptor and inhibit it. Autodock software was used and standard protocol of docking was carried out by selecting grid of X:Y:Z (60:60:60). Other insilico properties were calculated using Molinspiration online property calculator, Protox II for structural property calculation and acute oral toxicity determination respectively. Results revealed though the ligand molecule was safe but not solely effective for MAO inhibition. Derivatization in the molecule is must increasing its biological potential. Keywords: Depression, Docking, pyrazoline, Insilico toxicity determination